Addressing Multiple Ions Using Single Optical Probe: Multi‐Color Response via Mutually Independent Sensing Pathways. Issue 2 (10th January 2020) - Dey, Nilanjan; Bhattacharjee, Subham; Bhattacharya, Santanu
Abstract: Multiresponsive smart optical probe based on p‐phenylene vinylene backbone is designed for simultaneous sensing of multiple ions, such as Cu 2+, Zn 2+ and F − at pH 7.4. A rapid color change from colorless to deep yellow is observed upon addition of both Cu 2+ and Zn 2+ ion. However, under long UV lamp, the green‐colored emission of the probe is specifically quenched in the presence of Cu 2+, while Zn 2+ induces change in the emission color from green to yellow. On the contrary, F −, unlike Cu 2+ and Zn 2+, does not render any change in visible color, however, an emission quenching, similar to that of Cu 2+ addition, was noticed. The binding of metal ions to the central bipyridine core diminishes the 'conformational flexibility' and facilitates 'ligand to metal ion' charge transfer. On the contrary, addition of fluoride triggers the cleavage of silyl ether groups and results in the photo‐induced electron transfer from free hydroxyl groups to the core aromatic unit. Thus, we can detect as well as discriminate these three ions (Cu 2+, Zn 2+ and F − ) simultaneously by comparing the respective output signals. Further, a sustainable strategy has been developed for on‐site detection of toxic ions using reusable, low‐cost paper strips. Most importantly, the current method is found to be fairly effective in quantifying (as evident by relatively smaller standard deviation values) the presence of toxic metal ions, above permissible levels, in a wide range of natural water samples. Further, estimation of fluoride is achieved in commercially available toothpaste and mouthwash products. Abstract : Multiresponsive smart optical probe based on p‐phenylene vinylene backbone is designed for simultaneous detection of multiple ions, such as Cu 2+, Zn 2+ and F − at pH 7.4. The binding of metal ions to the central bipyridine core diminishes the 'conformational flexibility' of the compound and facilitates 'ligand to metal ion' charge transfer. On the contrary, the addition of fluoride triggers cleavage of silyl ether bonds and results in the photo‐induced electron transfer.